From Play to Projects: A Creative Pbl Model For Advancing Literacy In Early Childhood - Luluk Arifatur Rahmatin; Imron Arifin; Pramono Pramono (Institut Agama Islam An-Nawawi Purworejo, 2025)
This research aims to analyze the application of the Project Based Learning model to improve early childhood literacy. This study uses a qualitative case study type method where researchers explore phenomena related to the PBL learning model in improving children’s literacy. Data collection techniques are carried out through interviews, observations and documentation. Data analysis is done through data display, reduction, and conclusion. The study results indicate that PBL learning in improving children’s literacy is carried out in a planned and systematic manner with stages: enjoyable and contextual learning, use of technology in PBL, strengthening critical thinking skills and creativity, and involving parents in literacy projects. Parental involvement in literacy activities has also strengthened children’s motivation and understanding of the material being studied. This study provides implications for developing early childhood education through implementing effective Project Based Learning (PBL) to improve literacy. Parental involvement and the use of technology strengthen children’s motivation and understanding.